Analysis of the Current State of Hazelnut Processing Plants in Ordu - Derya Öztürk; Sezer Yıldız; Elif Topsakal (Turkish Journal of Agriculture: Food Science and Technology)
Turkey has almost 70% of world hazelnut production and 80% of hazelnut export. Ordu has the privilege of being the city which has the greatest area with hazelnut by supplying the 33.7% of hazelnut production. The income source of 70% of the people in Ordu is hazelnut and for this city, hazelnut is not only an agricultural product, it is also a national asset. There are 40 hazelnut processing plants with an internal capacity of 350.000 tons annually. 32.5% of these plants are in Ordu. When the top 20 Black Sea Hazelnut and Products Exporters Union member firms with the highest hazelnut export in 2016 were analyzed, it was found that 7 of these firms are in Ordu. These 7 firms in Ordu cover the 11.84% of the total hazelnut export value, which is 1.981.334.911$ for 2016. The purpose of this study which will be discussed within this context is to analyze and show the current states of hazelnut processing plants in Ordu in terms of product processing, quality assurance and standards and marketing. The data obtained as a result of the study will be used to find out the tendencies of the plants in the coming years. Because of this, the study is important in terms of researching the obstacles in increasing the export shares of hazelnut, which is one of the most important export products of Turkey economy. For this purpose, a face-to-face questionnaire was conducted with the managers and authorities of 12 hazelnut processing plants in Ordu. It is expected that the information presented within the context of the study will develop the hazelnut processing industry and will lead the related people researching in this field.